The European Union readmission policy after Lisbon - Mariagiulia Giuffrè (Interdisciplinary Political Studies, 2011)
This article conducts a brief historical excursus on the evolution of the EU’s readmission policy through the analysis of readmission agreements, meant as its main legal instruments. The Lisbon Treaty is herein portrayed as an historical watershed in the recognition of both an express competence of the Union with regard to measures aimed to address the readmission of irregular migrants, and a new role of the Parliament entrusted with the fundamental power to be consulted before a readmission agreement is definitively concluded by the Council.Finally, while a scrutiny of the close relationship between national and supranational readmission strategies reveals the unwillingness of Member States to renounce their national readmission policies, a preliminary assessment of the potential role of the Charter of Fundamental Rights in the field of return of irregular migrants after Lisbon is performed.